The role of adipocytokines and their receptors in bladder cancer: expression of adiponectin or leptin is an independent prognosticator - Kashiwagi, Eiji (Am J Transl Res, 2020)
Adipocytokines such as leptin and adiponectin have functions in metabolism as well as the development and progression of various types of malignancies. However, little is known about their role in bladder cancer. In this study, we investigated whether leptin, adiponectin, and their receptors have an impact on bladder cancer outgrowth and the mechanisms involved. We performed immunohistochemistry for leptin, leptin receptor (Ob-R), adiponectin, and adiponectin receptors (AdipoR1, AdipoR2) in bladder cancer tissue microarrays. Wound healing assay and western blot were then performed in human bladder cancer lines. The positive rates (0 vs 1+/2+/3+) of Ob-R (P=0.004), adiponectin (P<0.001), AdipoR1 (P=0.016), and AdipoR2 (P<0.001) expression were significantly higher in bladder tumors than in benign urothelial tissues. Strong (3+) leptin expression tended to be present more often in tumors (10.2%; P=0.079) than in benign tissues (3.2%). Multivariate analysis revealed a lower risk of recurrence (hazard ratio [HR]=0.432; 95% confidence interval [CI]=0.198-0.942; P=0.034) in patients with an adiponectin-positive non-muscle-invasive tumor and a higher risk of progression (HR=5.148, 95% CI=1.190-22.273; P=0.028) in patients with a leptin-positive muscle-invasive tumor. Treatment of two bladder cancer cell lines with a synthetic adiponectin inhibited their migration and the expressions of phospho-NF-κB, NF-κB, snail, slug, Y-box-binding protein 1, and COX-2, whereas leptin showed reverse effects. Downregulation of adiponectin expression and upregulation of leptin expression were independent predictors for the recurrence of non-muscle-invasive bladder tumors and progression of muscle-invasive bladder tumors, respectively. In summary, synthetic adiponectin might exhibit antitumor activity against bladder cancer.